El rol del espacio en la clarificación de los materiales sonoros en música acusmát - Federico Schumacher Ratti (Resonancias, 2015)
The space and the systematic control of sound’s movements and spatial trajectories in music, seems to be one of the most distinctive aspects of the acousmatic production mode, both for the production grammars and for the listener’s experience. Those who have a relationship with this musical practice as composers assign to this production grammars a major –if not essential– role in the syntactic clarity of acousmatic music, but it seems questionable whether this approach is shared by those who act as listeners of this kind of music. With this question in mind, I designed an experiment in order to contrast the composer’s statements with the perception of listeners. From the results of this experiment, though provisional, one might infer that in the listener’s experience those spatial production grammars have a mainly psychological, and just secondarily syntactic, role. In addition, the presence of those grammars in the acousmatic work seems to be an essential part of the emotional content of the acousmatic listening experience.